Conflict Mineral Disclosure Requirements. Issue 1 (November 2015) - Muriel, Leah
<x xml:space="preserve">Abstract</x> Under the Dodd‐Frank Act, U.S. publicly traded companies are now required to provide disclosures related to conflict minerals. These are specifically the minerals of tin, tantalum, tungsten, and gold that are obtained from the Democratic Republic of Congo and adjoining countries. Although a portion of the requirements were struck down and ruled as unconstitutional, certain inquiry and other due diligence measures are still required to be filed annually with the Securities and Exchange Commission (SEC). In addition, if a company voluntarily chooses to provide certain additional information, it will trigger a requirement for an independent audit of the Conflict Minerals Report filed with the SEC. © 2015 Wiley Periodicals, Inc.